Bulla Piusa VII De salute animarum a odradzający się Kościół katolicki na Pomorzu Zachodnim i ziemi lubuskiej - Grzegorz Wejman (Studia Koszalińsko-Kołobrzeskie)
The papal bull of Pope Pius VII De salute animarum of 16 July 1821 put in order the affairs of the Catholic Church in Prussia, including West Pomerania and Lubusz Land. Together with it, the face of the Catholic community, which in the Middle Ages was part of the Kamien (Kamień) Pomorski and Lubusz Bishoprics, and completely destroyed during the diaspora (starting from the mid-16th century), began to be reborn in its structures. The area of the former Kamien (Kamień) Pomorski Bishopric was subordinated to the Berlin Delegation, which was part of the Wrocław (Breslau) Diocese, which in 1930 was raised to the rank of a bishopric, and the areas of the former Lubusz Bishopric directly to the Wrocław (Breslau) Bishopric. When in 1821 there were three parishes within the Berlin Delegation (in Szczecin, Stralsund and Frankfurt (Oder)), already in the mid-19th century there were two archpresbyterates: Pomeranian with 10 parishes and Frankfurt with 7 parishes, and within the Wroclaw (Wrocław – Breslau) Diocese the Neuzelle Decanate with 5 parishes (covering the area of the former Lubusz Bishopric). Before the outbreak of World War II (1938), the face of Catholicism changed even more: the Berlin Bishopric already included 5 archpresbyterates: Szczecin (with 14 parishes), Stargard (11), Koszalin (8), Stralsund (8) and Frankfurt (6) and 4 parishes belonging to the Walcz (Wałcz) and Lębork Decanates, and within the Wroclaw (Wrocław – Breslau) Archdiocese there were two Decanates: Gorzow (Gorzów) (with 11 parishes) and Eberswald (2). In total, there were 64 parishes in the former Dioceses of Kamien (Kamień) Pomorski and Lubusz in 1938 (51 parishes in the area of the former Kamien (Kamień) Pomorski Diocese and 19 in the Lubusz Diocese), and in addition, 3 male religious congregations (with 3 monastic houses) and 5 female religious congregations (with 14 monastic houses) performed pastoral services here.